2nd International Conference on Sustainable Development Goals (ICSDG) 2019 - CGSS, Pusat Kajian Kelestarian Global (2019)
The 2019 International Conference on Sustainable Development Goals (ICSDG2019) aims at seeking strong collaboration and cooperation among all organisations worldwide in achieving the SDGs, with a theme of “Achieving SDGs: Rising to the Challenge”.